Mobile APP for facial recognition (Ciencias de la Ingeniería y Aplicadas, 2018)
Facial recognition technology allows individuals to be identified by analyzing facial characteristics that cannot be easily altered (the superficial arches, the areas around the cheekbones or the sides of the mouth). The technology is commonly used to compare real-time data shots of faces, even with movement, with stored templates, but it can also be used to compare static images such as those in passports. The facial identification process is basically divided into two tasks: detection and recognition. The first of them, detection, includes the location of one or more faces within an image, whether still or a video sequence. The second task, recognition, consists of comparing the face detected in the previous step with others previously stored in a database. These processes, detection and recognition, should not be totally independent because depending on the way in which a face is detected, it may be practically impossible to recognize it with faces from a database detected in a different way, hence recognition systems facial are strongly conditioned by the position and orientation of the subject's face with respect to the camera and the lighting conditions at the time of detection.
Keywords: Facial Recognition; Detection; Lightning; Technology